Penerapan Keadilan Restoratif Pada Kasus Kekerasan Dalam Rumah Tangga - Azizana, Zeniza Mar; Nur Azizah Hidayat (Faculty of Law, University of Muhammadiyaha Surabaya, 2023)
Domestic violence is a problem that has not abated. Many countries currently use a system of applying restorative justice in the completion of the criminal justice process to handle cases of domestic violence. According to Law Number 23 of 2004 concerning the Elimination of Domestic Violence, it proves that the settlement of domestic violence cases emphasizes how sanctions against perpetrators are criminal in nature but the preventive, protective, and consolidation objectives have not been fulfilled. The purpose of this study is to find out how criminal policy in Indonesia is in resolving domestic violence, to whether the application of restorative justice is appropriate for use in criminal justice in Indonesia while still referring to the legislation. This research is a normative juridical research that uses a statutory and conceptual approach. The results of this study indicate that the criminal law policy in Indonesia in the case of domestic violence has not shown a restorative approach. Which only focuses on criminal sanctions only.Keywords: Domestic violence, Crime, Restorative JusticeÂ Â